The atroviolacea Gene Encodes an R3-MYB Protein Repressing Anthocyanin Synthesis in Tomato Plants - Colanero, Sara; Perata, Pierdomenico; Gonzali, Silvia (Frontiers in Plant Science, 2018)
The anthocyanin biosynthetic pathway is well characterized in plants. However, in tomato (Solanum lycopersicum L.) an exhaustive knowledge of its regulation is still lacking. Tomato mutants showing higher levels of anthocyanins in fruits or vegetative tissues, such as Anthocyanin fruit (Aft) or atroviolacea (atv), have been extensively exploited in the attempt to clarify the process. Nevertheless, only candidate genes have been proposed as responsible for such phenotypes. The recessive atv mutation likely represents an allelic variant of a gene introgressed in tomato from wild Solanum species. We performed genome sequencing of atv/atv plants followed by candidate gene analysis, and identified a mutated gene encoding an R3-MYB protein. When overexpressed, this protein abolished anthocyanin production in tomato seedlings and plants, by silencing key regulators and biosynthetic genes of the pathway. The functional analysis of the protein clearly showed that it can negatively interfere with the activation of the anthocyanin biosynthetic pathway mediated by the endogenous MYB-bHLH-WDR (MBW) complexes. In particular, this R3-MYB protein can directly bind the bHLH factors which are part of the MBW complexes, therefore acting as a competitive inhibitor. The R3-MYB protein here described is therefore involved in a feedback mechanism that dampens the production of anthocyanins once activated by endogenous or exogenous stimuli. The atv mutation causes the production of a truncated version of the R3-MYB factor that cannot retain the full potential to inhibit the MBW complexes, thus leading to a constitutively higher production of anthocyanins.